Comparative study between salicylic acid and mandelic acid superficial chemical peelings in the treatment of acne vulgar: a bibliographic review (Research, Society and Development, 2022)
Introduction: Acne is a common skin problem that occurs through inflammation in the hair follicles. It is a chronic disease that can generate inflammatory, non-inflammatory or a mixture of both. It can appear in different regions of the body, but it usually affects the face more, thus having different reasons for its appearance. Objective: To better understand how the use of these two acids through treatment with chemical peels acts on the lesions caused by acne and what are the benefits presented on the skin. Methodology: The study was based on the methodology of integrative literature review, being of an exploratory nature, which is the analysis of information addressed previously, in a systematic and orderly manner. Result: All peels were well tolerated at the end of the study. Regarding adverse effects, there were not many complications and they were easily reversed. Furthermore, it was found that in summer the lesions worsened to the detriment of sweat, causing an increase in sebum in the hair follicles, resulting in a greater growth of Cutibacterium acnes. Final considerations: With all the analyzes carried out, it is deduced that the effectiveness between salicylic acid and mandelic acid peels is proportional to being used to treat acne vulgaris.